Comparing Spatial Heterogeneity of Bioavailable Nutrients and Soil Respiration in Boreal Sites Recovering From Natural and Anthropogenic Disturbance - Dietrich, Sebastian T.; MacKenzie, M. Derek (Frontiers in Environmental Science, 2018)
The mining of oil sands in Alberta, Canada is a large-scale disturbance that requires land reclamation to equivalent land capability. Cover soils used for upland forest reclamation are forest floor mineral-mix (FFM) sourced from upland forest ecosystems and peat mineral-mix (PM) sourced from lowland ecosystems. Spatial heterogeneity and quantity of soil resources, especially nutrient bioavailability, is important because it affects the establishment of native vegetation in forest ecosystems and soil respiration is an indicator for overall soil biologic activity. We studied spatial heterogeneity of soil nutrients as well as seasonal and spatial patterns of soil respiration in two sites reclaimed either with FFM or PM and two reference sites recovering either from harvest or fire. Contrary to our initial hypothesis, we identified spatial heterogeneity in some bioavailable nutrients in FFM and PM cover soil, indicating that standard placement processes can recreate spatial heterogeneity. However, some nutrients such as P, K and S showed no heterogeneity in PM at all. P and K availability was significantly lower and S was significantly higher in PM than in FFM and reference sites. Seasonal pattern of respiration showed variability on natural reference sites and on FFM, indicating that disturbance had not removed belowground function completely. PM reclaimed sites showed no strong seasonal respiration patterns indicating homogeneous belowground function. Surprisingly PM treatments were not characterized by highest rates of soil respiration while having highest amounts of total organic carbon. We conclude that FFM reclaimed sites may be more successfully reclaimed than PM sites because they are more similar to reference sites in terms of nutrient status and seasonal respiration patterns.